2016
DOI: 10.1021/acs.jchemed.6b00338
|View full text |Cite
|
Sign up to set email alerts
|

Activities in an S-STEM Program To Catalyze Early Entry into Research

Abstract: A cohort program to increase retention of under-represented groups in chemistry was developed at the College of Saint Benedict/Saint John’s University. In particular, this program chose to emphasize early career mentoring and early access to research. This goal was chosen because research has been repeatedly shown to increase scientific identity resulting in increased retention of students in the STEM fields. Several elements of this program have been useful in preparing students to access research programs ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, seven programs compared students who completed the bridge program with students in other courses without any control for prior academic ability ( Budny, 1992 ; Citty and Lindner, 2012 ; Cairncross et al , 2015 ; Nite et al , 2015 ; Pritchard et al , 2016 ; Tomasko et al ., 2016 ; Graham et al ., 2017 ), and two programs did not use a comparison group at all ( Raines, 2012 ; Harkins, 2016 ). Because prior academic ability is often a strong predictor of future GPA, it is important to control for a measure of prior academic ability to examine the impact of a program.…”
Section: Part 2 Goals Outcomes and Successes Of Stem Bridge Programentioning
confidence: 99%
See 1 more Smart Citation
“…However, seven programs compared students who completed the bridge program with students in other courses without any control for prior academic ability ( Budny, 1992 ; Citty and Lindner, 2012 ; Cairncross et al , 2015 ; Nite et al , 2015 ; Pritchard et al , 2016 ; Tomasko et al ., 2016 ; Graham et al ., 2017 ), and two programs did not use a comparison group at all ( Raines, 2012 ; Harkins, 2016 ). Because prior academic ability is often a strong predictor of future GPA, it is important to control for a measure of prior academic ability to examine the impact of a program.…”
Section: Part 2 Goals Outcomes and Successes Of Stem Bridge Programentioning
confidence: 99%
“…Four of these programs measured students’ participation in research, and all reported successfully meeting this goal. Three of these programs reported the number of students who had participated in their bridge programs who went on to participate in undergraduate research ( Gilmer, 2007 ; Russomanno et al , 2010 ; Windsor et al , 2015 ; Graham et al , 2017 ), and another program reported the number of former bridge students who went on to conduct PhD-level research ( Summers and Hrabowski, 2006 ; Maton et al , 2009 , 2012 , 2016 ; Stolle-­McAllister, 2011 ; Stolle-McAllister et al , 2011). Of note, most of these programs did not report a change in the percentage of students who were conducting research after implementing the bridge program and did not use a comparison group of students.…”
Section: Part 2 Goals Outcomes and Successes Of Stem Bridge Programentioning
confidence: 99%
“…Because we were most interested in relatively objective outcomes related to student performance, and due to the limits of the primary studies in this area, we did not consider attitudinal outcomes such as science motivation, science interest, and bridge program satisfaction. Rather, we focused on outcomes such as STEM major retention (e.g., Smith, 2017), STEM graduation rates (e.g., Kopec and Blair, 2014), math assessment scores (e.g., Ami, 2001), and class-specific GPAs (e.g., chemistry; Graham et al, 2016). Other outcomes considered in STEM bridge program research are general (non-STEM specific) academic outcomes, including time to graduate (e.g., Whalin et al, 2017), overall GPA (e.g., Graham et al, 2013), and university retention (e.g., Wischusen et al, 2011).…”
Section: Prior Research On Stem Bridge Programsmentioning
confidence: 99%
“…Because we were most interested in relatively objective outcomes related to student performance, and due to the limits of the primary studies in this area, we did not consider attitudinal outcomes such as science motivation, science interest, and bridge program satisfaction. Rather, we focused on outcomes such as STEM major retention (e.g., Smith, 2017 ), STEM graduation rates (e.g., Kopec and Blair, 2014 ), math assessment scores (e.g., Ami, 2001 ), and class-specific GPAs (e.g., chemistry; Graham et al. , 2016 ).…”
Section: A Meta-analysis Of University Stem Summer Bridge Program Effectivenessmentioning
confidence: 99%
“…Since the inception of S-STEM program, universities and colleges across the country have received support from this program through a competitive process [4][5][6][7][8] . The literature shows that the S-STEM program has generated positive impacts in undergraduate STEM education [4][5][6][7][8] . For example, Kalevitch et al created a Living-Learning Cohort model for the S-STEM students at their university 6 .…”
Section: Introductionmentioning
confidence: 99%